(Invited) Triple Phase Boundary Reaction in a Mixed-Conducting SOFC Cathode. (3rd May 2017) - Amezawa, Koji; Fujimaki, Yoshinobu; Mizuno, Keita; Kimura, Yuta; Nakamura, Takashi; Nitta, Kiyofumi; Terada, Yasuko; Iguchi, Fumitada; Yugami, Hiroo; Yashiro, Keiji; Kawada, Tatsuya
Abstract : The contribution of the triple phase boundary reaction in a mixed ionic and electronic conducting (MIEC) cathode in solid oxide fuel cells (SOFCs) was investigated. For this purpose, patterned thin film electrodes with or without triple phase boundaries, which simplified the microstructure of a practical porous electrode, were proposed and fabricated. In this work, an La0.6 Sr0.4 CoO3- δ (LSC) electrode on a Ce0.9 Gd0.1 O1.95 electrolyte was chosen as a model SOFC MIEC cathode. Effective reaction area was evaluated by means of operando micro X-ray absorption spectroscopy with the model electrodes under 10 -2 bar of p (O2 ) at 873 K. It was found that the introduction of triple phase boundaries shortened the effective reaction area. The results may indicate the non-negligible contribution of the triple phase boundary reaction even in SOFC MIEC cathodes.